Meta-heuristics for optimizing bi-objective heterogeneous urban traffic network - Tang, Zhe (2019)
Meta heuristic algorithms are often used to solve scheduling problems. In this project we will use the meta heuristic algorithm to solve the scheduling problem of urban traffic signals. The project uses a macro model of the two mixed flow of pedestrian and vehicle to analyze the delay of pedestrians and vehicles in the traffic network. The objective is to reduce the overall waiting time for vehicles and pedestrians. And a search operator is used to improve the performance of the meta-heuristics. Performance evaluation includes waiting time and computing time. The parameters involved in the related algorithms will be enumerated. A detailed comparison process will also be given.